TEORI EFISIENSI DALAM EKONOMI ISLAM - Ahmad Arisatul Cholik (University of Darussalam Gontor, 2013)
Lately, there are some economists who criticize the theory of efficiency. They argue that the current efficiency has deviated from first khittah and only beneficial for some people and hurt others. They just thinking of their welfare themselves without thinking about where the boundaries should be considered. They are influenced by western worldview that tends materialistic. This study aims to explore theory in Islamic Economics efficiency, so it can be reapplied in life in today’s modern era. In this study, researchers found that in Islam, efficiency theory has been applied since the time of Prophet Muhammad. Islam fully supports the efficiency in work, but all of it must remain in the corridor of Islamic law from the Qur’an and Sunah.